Danggui Sini decoction alleviates oxaliplatin-induced peripheral neuropathy by regulating gut microbiota and potentially relieving neuroinflammation related metabolic disorder - Chen Chen; Jian-Lin Xu; Zhan-Cheng Gu; Shan-Shan Zhou; Guo-Li Wei; Jia-Lin Gu; Hai-Long Ma; Yan-Qi Feng; Zi-Wei Song; Zhan-Peng Yan; Shan Deng; Rong Ding; et al. (BMC, 2024)
Abstract Background Danggui Sini decoction (DSD), a traditional Chinese medicine formula, has the function of nourishing blood, warming meridians, and unblocking collaterals. Our clinical and animal studies had shown that DSD can effectively protect against oxaliplatin (OXA)-induced peripheral neuropathy (OIPN), but the detailed mechanisms remain uncertain. Multiple studies have confirmed that gut microbiota plays a crucial role in the development of OIPN. In this study, the potential mechanism of protective effect of DSD against OIPN by regulating gut microbiota was investigated. Methods The neuroprotective effects of DSD against OIPN were examined on a rat model of OIPN by determining mechanical allodynia, biological features of dorsal root ganglia (DRG) as well as proinflammatory indicators. Gut microbiota dysbiosis was characterized using 16S rDNA gene sequencing and metabolism disorders were evaluated using untargeted and targeted metabolomics. Moreover the gut microbiota mediated mechanisms were validated by antibiotic intervention and fecal microbiota transplantation. Results DSD treatment significantly alleviated OIPN symptoms by relieving mechanical allodynia, preserving DRG integrity and reducing proinflammatory indicators lipopolysaccharide (LPS), IL-6 and TNF-α. Besides, DSD restored OXA induced intestinal barrier disruption, gut microbiota dysbiosis as well as systemic metabolic disorders. Correlation analysis revealed that DSD increased bacterial genera such as Faecalibaculum, Allobaculum, Dubosiella and Rhodospirillales_unclassified were closely associated with neuroinflammation related metabolites, including positively with short-chain fatty acids (SCFAs) and sphingomyelin (d18:1/16:0), and negatively with pi-methylimidazoleacetic acid, l-glutamine and homovanillic acid. Meanwhile, antibiotic intervention apparently relieved OIPN symptoms. Furthermore, fecal microbiota transplantation further confirmed the mediated effects of gut microbiota. Conclusion DSD alleviates OIPN by regulating gut microbiota and potentially relieving neuroinflammation related metabolic disorder.